Teaching Patient-Centered Care Through the Veterans History Project. Issue 6 (November 2018) - Vessey, Judith A.; Wendt, Judith; Glynn, Donna M.; McVey, Cecilia
Abstract : Determining the best ways to teach military culture and the veteran experience to nursing students and new nurses is an essential component in developing a culturally sensitive nursing workforce. The purpose of this article is to describe a theory-driven, experiential learning approach to integrating the Veterans History Project into the curricula for a postbaccalaureate nurse residency program. Participants acknowledged that this educational project better prepared them to care for the veteran population.